The exchange regime and trade balance in Turkey. Issue 4 (8th August 2018) - Cergibozan, Raif; Ari, Ali
ABSTRACT: Over the last 15 years, high trade deficits have become a source of external vulnerability for the relatively stabilized Turkish economy. This corresponds to the period where authorities have been following a floating exchange rate regime. Thus, this study aims to empirically show whether the adopted exchange rate regime has an impact on the trade balance for the period of 1987 Q1 to 2015 Q2. Estimation results indicate that there is a long-run relationship between the real effective exchange rate and trade balance under both fixed and floating regimes in Turkey, but there is no evidence for the J-curve hypothesis.